Leafminer insecis (Diptera: Agromyzidae) from the Sabana de Bogota (Cundinamarca, Colombia) - SANABRIA DE ARÉVALO, ISABEL (Revista Colombiana de Entomología, 1994)
The present work deals with a taxonomic study of adult leafminers (Diptera: Agromyzidae) from the Sabana of Bogotá. Specimens of 35 species were collected in the following 10 genera:Melanagromyza (4 species). Ophiomyia (3), Japanagromyza (1), Amauromyza (2), Cerodontha(2),Liriomyza (19), Calycomyza (1), Phytoliriomyza (1), Phytamyza(1) and Chromatomyia (1). Nineteen of these species were already known from this zone; five(5) are new records; nine(9) new species: two (2) of Ophiomyia, and seven (7) of Liriomyza were described; two (2) species of the genus Melanagromyza possible new, are been studied. Keys to genera and species are provided; notes on host plants, distribution and Colombian literature of some of them are given.